2009
DOI: 10.1186/1475-9276-8-43
|View full text |Cite
|
Sign up to set email alerts
|

Towards equitable access to medicines for the rural poor: analyses of insurance claims reveal rural pharmacy initiative triggers price competition in Kyrgyzstan

Abstract: BackgroundA rural pharmacy initiative (RPI) designed to increase access to medicines in rural Kyrgyzstan created a network of 12 pharmacies using a revolving drug fund mechanism in 12 villages where no pharmacies previously existed. The objective of this study was to determine if the establishment of the RPI resulted in the unforeseen benefit of triggering medicine price competition in pre-existing (non-RPI) private pharmacies located in the region.MethodsWe conducted descriptive and multivariate analyses on m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…While we have not presented the analysis in this paper, we found that profit at the individual pharmacy level varied, with some pharmacies performing better than others [ 36 ]. Not surprisingly, pharmacies located in villages with larger populations enjoyed greater profits than those in less-populated villages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While we have not presented the analysis in this paper, we found that profit at the individual pharmacy level varied, with some pharmacies performing better than others [ 36 ]. Not surprisingly, pharmacies located in villages with larger populations enjoyed greater profits than those in less-populated villages.…”
Section: Discussionmentioning
confidence: 99%
“…There is no evidence to suggest wholesalers engaged in rebate and bundling practices that are common in developed countries [ 39 , 40 ]. Finally, we present current medicine prices in lieu of adjusting prices for inflation after noting that most medicine prices outside the pharmacy network trended downward or remained unchanged over the four years [ 34 , 36 ] and did not seem to follow the overall national inflation rate of 10% [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CHE is a general term used to describe various health care expenditures that threaten households’ financial conditions to maintain their survival needs [ 5 ]. WHO defined CHE as health expenditures being more than 40% of household’s capacity to pay (CTP) [ 6 , 7 ]. In the past decade, great achievements have been made in the National Health System Reform (NHSR) with significant improvement of access, quality and equity of health services, but there are also challenges that cannot be ignored, such as the roaring health-care costs.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, major concerns with regard to equity and accessibility remain [8]. First, since a high proportion of the population lives in rural Kyrgyzstan, ensuring access to health care-including medicinesin remote areas is a challenge [9,10]. Second, out-of-pocket (OOP) payments for health services have been steadily increasing in the new millennium, with considerable growth in the financial burden after 2009, in particular for the poorest population groups and in the two largest cities -Bishkek and Osh [11,12].…”
Section: Introductionmentioning
confidence: 99%